The Strategy of Islamic Education Teachers in Instilling Student Moral Values at State Vocational High School 6 Sukoharjo Indonesia - Purwasari, Dharma Ratna; Waston, Waston; Rochim Maksum, Muh. Nur (Walidem Institute and Publishing, 2023)
Cultivation of morals is an effort to replace bad morals with good morals, and to increase good morals so that students understand and can feel that noble morals can be imprinted in individuals. In data collection, the authors conducted a field study using data collection methods in the form of interviews, observation, and documentation. Based on the results of the research, the authors can conclude that the strategies of Islamic Education Teachers in cultivating students' morals at SMK Negeri 6 Sukoharjo are habituation, motivation, exemplary, story, giving a picture of surge and hell, reward and punishment. There are several factors supporting the cultivation of morals at SMK Negeri 6 Sukoharjo, namely the participation of all teachers, students have high enthusiasm, good coordination between Islamic Education teachers, the support of the principal in all activities and willingness to fulfil infrastructure and infrastructure needed in religious activities. The inhibiting factor faced by Islamic Education teachers in cultivating student morals at SMK Negeri 6 Sukoharjo is the different backgrounds of students. Every student has a different family background, and the lack of parental supervision at home and during the pandemic teacher monitoring of students is hampered. The results of the cultivation of morals by the Islamic Education Teacher towards students at SMK Negeri 6 Sukoharjo are considered successful, marked by a change in the child's attitude to be friendly, and polite. In addition, children are accustomed to praying at the beginning of time and already wear a headscarf for women. In addition, it is also supported by the scores of students' report cards, the majority of which have met the KKM.